Collecting the data but missing the point: validity of hand hygiene audit data. Issue 2 (June 2015) - Jeanes, A.; Coen, P.G.; Wilson, A.P.; Drey, N.S.; Gould, D.J.
Summary: Background: Monitoring of hand hygiene compliance (HHC) by observation has been used in healthcare for more than a decade to provide assurance of infection control practice. The validity of this information is rarely tested. Aim: To examine the process and validity of collecting and reporting HHC data based on direct observation of compliance. Methods: Five years of HHC data routinely collected in one large National Health Service hospital trust were examined. The data collection process was reviewed by survey and interview of the auditors. HHC data collected for other research purposes undertaken during this period were compared with the organizational data set. Findings: After an initial increase, the reported HHC remained unchanged close to its intended target throughout this period. Examination of the data collection process revealed changes, including local interpretations of the data collection system, which invalidated the results. A minority of auditors had received formal training in observation and feedback of results. Conclusion: Whereas observation of HHC is the current gold standard, unless data collection definitions and methods are unambiguous, published, carefully supervised, and regularly monitored, variations may occur which affect the validity of the data. If the purpose of HHC monitoring is to improve practice and minimize transmission of infection, then a focus on progressively improving performance rather than on achieving a target may offer greater opportunities to achieve this.